Ammonia and Nitrous Oxide Emissions from Broiler Houses with Downtime Windrowed Litter. Issue 3 (1st May 2017) - Ro, Kyoung S.; Moore, Philip A.; Szogi, Ariel A.; Millner, Patricia D.
Abstract : An emerging poultry manure management practice is in‐house windrowing to disinfect the litter. However, this practice is likely to increase emissions of ammonia (NH3 ) and nitrous oxide (N2 O) from the windrowed litter. The objective of this study was to quantitatively compare NH3 and N2 O emissions from broiler houses with and without in‐house windrowing. Two broiler houses at a commercial farm were used to compare the NH3 and N2 O emissions. Gas emission measurements were conducted continuously and simultaneously for both the control house (without windrowing) and the house with windrowing during the same production periods. The house emission rates were calculated by multiplying the hourly mean gas concentrations and the ventilation rates. The windrowed litter temperature was significantly higher than that of the control litter. The impact of downtime (the time lapse between flocks, during which the bird house is empty) windrowing litter on pathogen reduction was inconclusive because of very low or no recovery of both Escherichia coli and Salmonella spp. from control or windrowed litter samples, respectively. The windrowing house NH3 emissions were 26.2 and 16.6 kg d −1 house −1, whereas for the control house, they were 14.6 and 12.8 kg d −1 house −1 in 2012 and 2013, respectively. The N2 O emissions from the windrowing house were also higher than those from the control house. The total NH3 and N2 O emissions from broiler houses practicing windrowing litter management were estimated to be 35.0 and 4.43 g bird −1, respectively, compared with 31.9 and 3.89 g bird −1 for the control house, respectively. Core Ideas: Significantly high NH3 and N2 O emissions from a downtime windrowing house. 31% of NH3 and 16% of N2 O emissions per bird were attributed to windrowing litter.